Transcriptomic alterations underline aging of osteogenic bone marrow stromal cells - Cheng, Yu-Hao (World J Stem Cells, 2021)
BACKGROUND: Multipotent bone marrow stromal cells (BMSCs) are adult stem cells that form functional osteoblasts and play a critical role in bone remodeling. During aging, an increase in bone loss and reduction in structural integrity lead to osteoporosis and result in an increased risk of fracture. We examined age-dependent histological changes in murine vertebrae and uncovered that bone loss begins as early as the age of 1 mo. AIM: To identify the functional alterations and transcriptomic dynamics of BMSCs during early bone loss. METHODS: We collected BMSCs from mice at early to middle ages and compared their self-renewal and differentiation potential. Subsequently, we obtained the transcriptomic profiles of BMSCs at 1 mo, 3 mo, and 7 mo. RESULTS: The colony-forming and osteogenic commitment capacity showed a comparable finding that decreased at the age of 1 mo. The transcriptomic analysis showed the enrichment of osteoblastic regulation genes at 1 mo and loss of osteogenic features at 3 mo. The BMSCs at 7 mo showed enrichment of adipogenic and DNA repair features. Moreover, we demonstrated that the WNT and MAPK signaling pathways were upregulated at 1 mo, followed by increased pro-inflammatory and apoptotic features. CONCLUSION: Our study uncovered the cellular and molecular dynamics of bone aging in mice and demonstrated the contribution of BMSCs to the early stage of age-related bone loss.